Síntese de novos compostos organosselênicos com potencial atividade antimicrobiana e antitumoral - Huang, Min-Fu Nascimento (2016)
This work deals with the design, synthesis and characterization of organosselênicas molecules with potential antimicrobial and antitumor activity, for both were prepared a series of 12 unpublished organosselênicos compounds (bis-selenide) containing the amide function, synthesized from the chloride substitution reaction alkyl (with / or without substituents) with a nucleophilic selenium species prepared from the elemental selenium (Se0 amorphous) to give bis-selenide with programmatic variations in yields ranging from 72-85%. The structural characterization of the compounds is based on several experiments NMR 1H, NMR 13C and IR. In addition to the preparation and characterization studies pharmacokinetic evaluation in silico and a preliminary test facing cytotoxicity Artemia Salina Leach were performed. The results revealed that the two compounds SeA5 and Se2A5 respectively showed LD50 of 127 and 156 ppm. In general the studies forward to these new organosselênicos compounds obtained promising results when assessed theoretically in its oral availability and showing good pharmacological low toxicity profiles (Artemia Salina Leach, Osires). Another important factor was obtained to demonstrate the interaction of nitrogen Selenium type by NMR 1H spectra, this study generated significant information around organosselênicos compounds. Finally microbiological testing front bacteria and fungi, indicate great activity against Candida albicans gender for compounds SeA3 and Se2A3, who owned MIC 128 µg.